Non-Conformity in a Predominantly Heteronormative Space: Experiences of Lesbian University Students - Ndaba, Ntombikayise Dolly (University of the Witwatersrand, Johannesburg, 2024)
The freedom of expression and choice of gender of sexually nonconforming individuals is constantly impacted by restrictive societal norms and heteronormative standards. While there are numerous studies on gender and sexual diversity globally, the majority of these are studies conducted in the global north. There is limited research on sexual orientation and gender identity in the Southern African region and increasing academic inquiry into the experiences of sexual minority students. This research study aimed to understand the experiences of lesbian females within and outside of the university environment in South Africa. This study used a qualitative narrative approach and was informed by theories of heteronormativity, intersectionality, and narrative theory to first investigate and understand how lesbian students define and express their sexuality. The participants of this study all self- identified as lesbians and students from different fields and levels of study at the University of the Witwatersrand, Johannesburg. The data was collected through semi-structured individual interviews and analysed using narrative thematic analysis. The findings of this study reveal that individuals’ experiences of their sexual orientation identity vary depending on their contexts. In addition to their lesbian identity, individuals are constantly negotiating their intersecting identities, and this influences how they experience and are experienced in different environments. The university campus environment is one where most participants feel free to explore and express their sexuality. However, this freedom did not necessarily equate to feelings of safety or support, as there is a lack of confidence in the adequacy and effectiveness of the services available to assist and support lesbians in issues relating to same-sex relationships. This study contributes to the understanding of lesbian v students’ expression, experiences, and usefulness of the existing university efforts towards inclusivity.
A research report submitted in fulfillment of the requirements for the Master of Arts in Community-Based Counselling Psychology, In the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Nonconformity; heteronormativity; intersectionality; homosexuality; narrative theory; lesbian; SDG-5: Gender equality